Unlocking Peak Performance: How Motivation and Discipline Drive Success at the Directorate General of Agricultural Infrastructure and Facilities - Winarto, Pawit; Maemunah, Sari; Fitra, Muhammad; Surtinah , Wiwin; Istiatik, Dasih Irma (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
This research aims to explore the impact of motivation and work discipline on employee performance at the Directorate General of Agricultural Infrastructure and Facilities. It examines both the individual and combined effects of motivation and work discipline on staff performance. The study employs a survey method, collecting data through questionnaires distributed to employees of the Directorate General. The analysis includes simple and multiple regression, along with hypothesis testing using T-table and F-table, with data processed through SPSS Version 26. The findings reveal that both motivation and work discipline have a significant and positive impact on employee performance. Furthermore, when considered together, these factors also show a significant effect on performance. These results underline the importance of fostering both motivation and discipline within the workforce. The managerial implications highlight the need for leadership to focus on aligning employee goals with organizational objectives, ensuring that procedures and strategies support a motivated and disciplined team. By doing so, the Directorate General can significantly enhance staff performance and achieve its broader goals effectively.